Targeted filtering reduces the complexity of UHPLC-Orbitrap-HRMS data to decipher polyphenol polymerization. (15th July 2017) - Vallverdú-Queralt, Anna; Meudec, Emmanuelle; Eder, Matthias; Lamuela-Raventos, Rosa M.; Sommerer, Nicolas; Cheynier, Véronique
Highlights: Acetaldehyde-epicatechin reactions were studied by UHPLC-LTQ-Orbitrap-HRMS. Over 70 reaction products were detected by Van Krevelen diagrams and Kendrick plots. Phloroglucinolysis provided additional structural information on polymer building blocks. Ethyl-linked polymers up to 11 units and xanthylium derivatives were detected for the first time. A cascade reaction mechanism was proposed. Abstract: UHPLC-LTQ-Orbitrap-high resolution mass spectrometry (HRMS) was applied to investigate complex polymeric polyphenols, before and after acid-catalysed depolymerisation in the presence of a nucleophile (phloroglucinol). Reaction products of (−)-epicatechin with acetaldehyde formed in model solution were selected for a proof-of concept experiment. The complexity of the UHPLC-HRMS dataset obtained after 4 h incubation was reduced with petroleomics-inspired strategies using Van Krevelen diagrams and modified Kendrick mass defect filtering targeting ethyl-epicatechin (C17 H16 O6 ) units. Combining these approaches with mass fragmentation and phloroglucinolysis allowed us to describe reaction of epicatechin and acetaldehyde. More than 65 compounds were found, including the homogeneous bridged derivatives (up to the undecamer), vinyl and ethanol adducts, and xanthene and xanthylium salt derivatives which were identified for the first time.